Studi Permukiman Kuna di Indonesia Melalui Pendekatan Multidisiplin - Djoko Dwiyanto (Balai Arkeologi Yogyakarta, 1994)
Research in archaeology has recently grown rapidly in line with the development of science and technology. This development is not only evident from the selection of sites, the application of theory and methodology, the use of methods and techniques, but also the selection and appearance of research subjects. Archaeology, which at the beginning of its development was only known as a hobby, is not surprising if the focus of attention was initially focused on objects that have artistic value. In subsequent developments observers are not only interested in objects that have artistic value, but also those that have no artistic value and even reach a level of attention to the complexities of relations between objects that can reflect various aspects of human life in the past.